The Role of Novel Biomarkers in Early Diagnosis and Prognosis of Acute Kidney Injury in Newborns - Argyri, Ioanna; Xanthos, Theodoros; Varsami, Marianna; Aroni, Filippia; Papalois, Apostolos; Dontas, Ismene; Fanos, Vassillios; Iacovidou, Nicoletta (American Journal of Perinatology, 2013)
Acute kidney injury (AKI) refers to the rapid loss of renal function. In clinical practice, AKI is common among hospitalized patients of all age groups including neonates and remains an important cause of morbidity and mortality due to its late diagnosis and therefore delayed therapeutic intervention. Although the precise incidence of AKI in newborn is unknown, several studies have reported that 8 to 24% of all critically ill newborns in neonatal intensive care units may develop the condition. We aim at reviewing the existing literature on novel serum and urinary biomarkers and discuss their role in the early diagnosis and prognosis of AKI in newborns. Specifically, this review will focus on cystatin C (CysC), neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-18 (IL-18) in serum and on CysC, NGAL, kidney injury molecule-1, and IL-18 in urine.
Keywords: acute kidney injury; newborns; biomarkers; creatinine